High-Intensity Interval Training and Moderate-Intensity Continuous Training Attenuate Oxidative Damage and Promote Myokine Response in the Skeletal Muscle of ApoE KO Mice on High-Fat Diet - Linjia Wang; Jessica Lavier; Weicheng Hua; Yangwenjie Wang; Lijing Gong; Hao Wei; Jianxiong Wang; Maxime Pellegrin; Grégoire P. Millet; Ying Zhang (MDPI AG, 2021)
The purpose of this study was to investigate the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on the skeletal muscle in Apolipoprotein E knockout (ApoE KO) and wild-type (WT) C57BL/6J mice. ApoE KO mice fed with a high-fat diet were randomly allocated into: Control group without exercise (ApoE−/− CON), HIIT group (ApoE−/− HIIT), and MICT group (ApoE−/− MICT). Exercise endurance, blood lipid profile, muscle antioxidative capacity, and myokine production were measured after six weeks of interventions. ApoE−/− CON mice exhibited hyperlipidemia and increased oxidative stress, compared to the WT mice. HIIT and MICT reduced blood lipid levels, ROS production, and protein carbonyl content in the skeletal muscle, while it enhanced the GSH generation and potently promoted mRNA expression of genes involved in the production of irisin and BAIBA. Moreover, ApoE−/− HIIT mice had significantly lower plasma HDL-C content, mRNA expression of MyHC-IIx and Vegfa165 in EDL, and ROS level; but remarkably higher mRNA expression of Hadha in the skeletal muscle than those of ApoE−/− MICT mice. These results demonstrated that both exercise programs were effective for the ApoE KO mice by attenuating the oxidative damage and promoting the myokines response and production. In particular, HIIT was more beneficial to reduce the ROS level in the skeletal muscle.